Determining low back pain factors and effects on daily activities in operating room personnel in Türkiye - GÜLEÇ, Habibe; Karahan, Azize (International Journal of Occupational Safety and Health, 2023)
Introduction: Low back pain is a common problem among operating room personnel. The study was performed to determine low back pain (LBP) factors and effects on daily activities in operating room personnel. Methods: The descriptive study was conducted in January 2018 in Ankara, Türkiye. The study sample consisted of 210 operating room personnel. Data from the study were collected using the Oswestry Low Back Pain Disability Questionnaire and Socio-Demographic Characteristics and Low Back Health Question Form. Results: The majority of operating room personnel had LBP. The mean disability score of the Operating room personnel was 9.69±6.49. A total of 8.1% of operating room personnel had severe disabilities. The disability score of the operating room personnel was higher in women, nurses, and personnel who worked over 8 hours a day, those who had any level of stress, and those who lifted patients without assistance. Conclusion: LBP remains an important problem in operating room staff and negatively affects daily activities. Considering the disability caused by LBP, to prevent LBP, developing comprehensive programs with hospital management including exercise, coping with stress, smoking cessation, and regulation of the working environment and conditions is suggested.